Thermal Analysis of Medium Voltage Single Core Armoured XLPE Cable - Mohamed A Alsharif; Khlid Ben Hamad; Abdulgader Alsharif; Mohamed Salem (African Journal of Advanced Pure and Applied Sciences, 2026)
Worldwide, electricity distribution networks primarily rely on medium-voltage cross-linked polyethylene underground cables. The thermal performance of these cables is critical to their operational stability and service lifespan, with operating temperature and thermal history being the key influencing factors. This paper presents an accurate thermal model for a buried single-core armoured cross-linked polyethylene medium-voltage cable system, developed using the finite element method. Key parameters, such as ampacity, cable construction, installation configuration, the thermal characteristics of the surrounding soil, and the prevailing ambient temperature, are considered. The thermal field response under both steady-load and realistic time-varying load conditions, including daily load variations, is investigated. Electrical losses are calculated and integrated into the thermal analysis. The simulation results reveal significant time-dependent temperature gradients and cyclic thermal variations within the cable, highlighting the necessity of transient thermal analysis. This study contributes to a deeper understanding of the modelling and analysis of thermal behaviour of buried armoured cross-linked polyethylene cables, enabling improved assessment of plant integrity and the extension of service life.